Evolutionary history of plant microRNAs - Taylor, R; Tarver, J; Hiscock, S; Donoghue, P (Elsevier, 2014)
microRNAs (miRNAs) are short noncoding regulatory genes that perform important roles in plant development and physiology. With the increasing power of next generation sequencing technologies and the development of bioinformatic tools, there has been a dramatic increase in the number of studies surveying the miRNAomes of plant species, which has led to an explosion in the number of described miRNAs. Unfortunately, very many of these new discoveries have been incompletely annotated and thus fail to discriminate genuine miRNAs from small interfering RNAs (siRNAs), fragments of longer RNAs, and random sequence. We review the published repertoire of plant miRNAs, discriminating those that have been correctly annotated. We use these data to explore prevailing hypotheses on the tempo and mode of miRNA evolution within the plant kingdom.